Моделирование оценки рисков травмирования на предприятии - Евтушенко, Ольга Владимировна (My University, 2013)
Для моделирования оценки рисков травмирования на предприятии, предложена матрица расчёта количественных показателей рисков по каждой причине и виду события. To model the risk assessment of injury in the enterprise, proposed matrix calculation of quantitative risk indicators for each cause and the type of event that is contained in the form of mandatory annual statistical reports and traditionally analyzed separately, independently of each other.
Keywords: безопасность труда; риск травматизма; несчастный случай; risk of injury; type of risk; accidents; кафедра екології та екоменеджменту